Reproductive biology of three gadiform fish species through the Mediterranean deep-sea range (147-1850 m) - Rotllant, Guiomar; Moranta, Joan; Massutí, Enric; Sardà, Francisco; Morales-Nin, Beatriz (Scientia Marina, 2002)
Knowledge of deep-sea reproductive biology is slight and interpretations of reproductive strategies in deep-sea fishes are controversial. Since the Mediterranean is a fairly stable and constant sea, we might expect a consistent pattern of reproduction of deep-sea species. Three gadiforms species with a succesive bathymetric and an ecological and economical importance in the Mediterranean fishing industry, Phycis blennoides, Mora moro and Lepidion lepidion, were selected for the present study. These three species of gadiforms are sexually dimorphic and their reproductive population is located at the lower zone of their bathymetric range. Females were always bigger than males. The smallest mature male was observed at 19, 32 and 18 cm TL (total length) and the smallest mature female at 20, 34 and 20 cm TL for P. blennoides, M. moro and L. lepidion respectively. The three species are iteroparous and females could be all-at-once or batch-spawners. An autumn mature season was observed for P. blennoides, whereas M. moro and L. lepidion had mature individuals all year round except in summer. Hence, physical constancy at greater depths is able to lengthen the reproductive season and the deepest species has a quasi-continuous reproductive pattern. Similar reproductive tissues have been found in the three species studied, and they show analogous structure with other deep-sea gadiforms and their shallow-water congeners.